Marxism in the Philippines : Marx centennial lectures - Nemenzo, Francisco; Fer, Anna; Malay Jr., Armando; Bolasco, Mario (Quezon City : Third World Studies Center, 1984)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: marxisme; Filipijnen